Geomapping of trematode-induced granulomatous anterior uveitis - a newly identified cause of blindness among children in the Pudukkottai district of the Tamil Nadu State, India (Geospatial Health, 2009)
There is evidence that a specific type of allergic conjunctive-uveal granuloma reported from South India could be due to infection by a trematode parasite. In these patients, the histopathological examination of the eye reveals a zonal granulomatous inflammation with purulent material including structures displaying evidence of trematode infection. To investigate this further, medical records describing such cases in the Pudukkottai district, Tamil Nadu State, India, covering the period 2001-2005, were collected. Since trematodes require a snail intermediate host for completing the life cycle, ponds frequently used for bathing in the area were inspected to identify a possible culprit. The hypothesis that ponds with snail habitats could be the source of infection was supported by the finding of a positive correlation between the geographical distribution of patients' residencies and the location of such ponds. Geographic information systems (GIS) were used to study the spatial distribution of ponds and patients, while satellite-based remote sensing (RS) was applied to attempt finding a parameter characteristic for ponds with snail habitats that could facilitate risk-identification over larger areas. It was found that ponds carrying risk could be differentiated from others through analysis of their spectral surface properties. This pond classification approach, confirmed by field visits, could thus become a useful tool for the location of snail habitats constituting risk as predicted.